Mendirikan Ekosistem Pangan Desa: Sinergi BUMDesa, Pemetaan Potensi, dan Platform Digital - Amali, Lanto Ningrayati; Katili, Muhammad Rifai; Yahya, Lailany; Tuloli, Mohamad Syafri (Universitas Negeri Gorontalo, 2025)
This community service program aimed to strengthen the role of Village-Owned Enterprises (BUMDesa) in enhancing food security based on local potential in Panggulo Village, Botupingge District, Bone Bolango Regency. Key challenges included the inactive status of BUMDesa, limited public awareness of food security, lack of local potential mapping, and the absence of digital platforms for product promotion. The program was implemented through a participatory, asset-based approach in five stages: problem identification, potential mapping, training, digitalization, and mentoring. Results showed significant improvements in BUMDesa management capacity, the development of two flagship local food products, the launch of a village website, and increased community awareness. The program demonstrated that integrating institutional strengthening, community empowerment, and digitalization is an effective strategy for developing sustainable village-level food security systems.